THE EFFECT OF USING ENGLISH SONGS ON THE STUDENTS’ SPEAKING SKILL - Mustakim Sagita, Ramlan, Nora Vita (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Jabal Ghafur, 2020)
The objective of the study was to get the empirical data about the effect of using song on students’ speaking skill at the second year students of SMP Negeri 1 Mila, Pidie. The method of this study was quantitative method. To get the sample, researcher used random sampling as the technique. The sample of this study were class VIII.B as the experimental class and VIII.A as the control class. Both of the class were consisted of 22 students. In collecting the data, the researcher conducted pre test and post test by asking students singing songs. In the control class, the result of pre test(x1) score was 1285. The result of post test(x2) score was 1462. The gained(dx) both of pre test and post test was 182. The mean(Mx) score was 8,2. in the experimental class, the result of pre test(y1) score was 1190. The result of post test(y2) score was 1608. The gained(dy) both of pre test and post test was 418. The mean(My) score was 19. The testing of hypothesis was analyzed using t-test formula. The result ttest (t0) both of the classes was 3,14. The result of this study showed that there was significant difference on students’ speaking skill that was taught by using English song. In the table of significance, it could be seen on the significance degree or ? = 0.05 and df=42. The ttable (t095(42))=2,68. Then, by comparing the result t0 is bigger than ttable, that is 3.14 > 2,68. The hypothesis (Ha) was accepted and the null hypothesis (Ho) was rejected. It can be concluded that the using of English song was effective in teaching speaking.Key words: Speaking, English song.